Layered SnS2‐Reduced Graphene Oxide Composite – A High‐Capacity, High‐Rate, and Long‐Cycle Life Sodium‐Ion Battery Anode Material. (27th March 2014) - Qu, Baihua; Ma, Chuze; Ji, Ge; Xu, Chaohe; Xu, Jing; Meng, Ying Shirley; Wang, Taihong; Lee, Jim Yang
<x xml:space="preserve">Abstract</x> A layered SnS2‐reduced graphene oxide (SnS2‐RGO) composite is prepared by a facile hydrothermal route and evaluated as an anode material for sodium‐ion batteries (NIBs). The measured electrochemical properties are a high charge specific capacity (630 mAh g−1 at 0.2 A g−1) coupled to a good rate performance (544 mAh g−1 at 2 A g−1) and long cycle‐life (500 mAh g−1 at 1 A g−1 for 400 cycles). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>